(untitled) (Global Journal of Management and Business Research, 2016)
In this study researchers evaluate fund specific and comparative risk adjusted performance of open ended equity growth schemes and also assess relative efficiency of select mutual fund schemes. Daily Net Asset Values (NAVs) of 17 funds for a period of eight years are gathered. Data are transformed using Log Normal method. Risk adjusted performance is measured using Sharpe index, comparative analyses are conducted using analysis of variance and t-test. Finally relative efficiency is measured with Data Envelopment Analysis (DEA). The study results report that, of the eight years, sample schemes reported positive risk adjusted returns for four years, and for remaining four years fund returns are negative. Researchers failed to find any difference in the performance among schemes. Furthermore, there is no difference in the performance of small cap and large cap fund schemes. Relative efficiency performance is also not statistically significant.